Bloodstain pattern evidence : objective approaches and case applications - Wonder, Anita Y. (Medicine and Dentistry 2007 : Subject Collection, 2007)
In Bloodstain Pattern Evidence, the concepts introduced in the author's first book, Blood Dynamics, are updated and applied to provide essential answers in the resolution of actual crimes. The book is accessible to all levels of investigators, regardless of academic background, and allows readers to develop a fundamental understanding of the underlying scientific principles behind bloodstain pattern evidence. Bloodstain Pattern Evidence builds on the fundamental ideas brought about by an understanding of Non-Newtonian dynamics, and illustrates through case work the practical forensic science.